2020
DOI: 10.1007/s12070-020-02224-x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Crisis During COVID 19: Online Classes, a Panacea for Imminent Doctors

Abstract: Introduction COVID 19 made a serious impact on many aspects of everyday life. The world saw a paradigm shift in the education system favouring online learning during the constrains of pandemic. Methodology To assess the attitude of the students towards online learning in subject of ENT, we conducted an observational study among 170 third year MBBS undergraduate students of our institute attending online classes through the student portal of our university website. Results Our survey revealed students favoured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 8 publications
(16 reference statements)
6
50
2
Order By: Relevance
“…However, web-based classes cannot provide such opportunities, which may add to medical students' worries about their academic achievements and result in high amounts of mental stress. Students have been reported to prefer studying in classrooms over having web-based classes due to the feeling of being together during classroom learning and the ability to share perspectives [6]. Therefore, the lack of peer contact and face-to-face communication with teachers in web-based classes may increase the risk of developing worry, anxiety, or even depression among medical students.…”
Section: Introductionmentioning
confidence: 99%
“…However, web-based classes cannot provide such opportunities, which may add to medical students' worries about their academic achievements and result in high amounts of mental stress. Students have been reported to prefer studying in classrooms over having web-based classes due to the feeling of being together during classroom learning and the ability to share perspectives [6]. Therefore, the lack of peer contact and face-to-face communication with teachers in web-based classes may increase the risk of developing worry, anxiety, or even depression among medical students.…”
Section: Introductionmentioning
confidence: 99%
“…In study conducted by Shetty et al, medical students preferred a combined online and classroom learning approach for their better academic development. 13 Rajab et al, in their study on challenges in online medical education found out that about 62.5% preferred blended conventional and online method of teaching, while only 25.5% preferred face to face instruction. 14 In another study on pharmacy students and faculty, done by Syofyan et al, majority favoured blended learning over fully online or face to face lectures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors added that students missed several aspects of anatomy education, such as dissection lab, histology lab, face-to-face lectures, interaction with their mentors, and discussion with their classmates (Singal, Bansal et al 2020). A study done on undergraduate medical students in India revealed that about 31% of students prefer classroom learning only, 16% prefer online learning only while 53% prefer a combination of both methods (Shetty, Shilpa et al 2020). Students' preference of classroom learning is due to student teacher interaction, acquiring practical skills, and development of communication skills, while students' preference to online learning is due to its easy participation, and time investment (Shetty, Shilpa et al 2020).…”
Section: Discussionmentioning
confidence: 99%